Four new species of Psychomyia (Trichoptera: Psychomyiidae) from China, with re-descriptions of two species - Peng, Lang; Wang, Bei-Xin; Sun, Chang-Hai (Zootaxa, 2020)
Four new species of the genus Psychomyia from China are described, illustrated and diagnosed: P. complexa n. sp. (Zhe-jiang), P. conoidea n. sp. (Zhe-jiang), P. obtorta n. sp. (Jiang-xi), and P. tripetala n. sp. (Jiang-xi). Two known species, P. martynovi Hwang 1957 and P. extensa Li, Sun & Yang 1999 are re-described and re-illustrated, with new distributional data.